Light scattering methods to test inorganic PCMs for application in buildings - De Paola, Maria Gabriela; Calabrò, Vincenza; De Simone, Marilena (IOP, 2017)
Thermal performance and stability over time are key parameters for the characterization and application of PCMs in the building sector. Generally, inorganic PCMs are dispersions of hydrated salts and additives in water that counteract phase segregation phenomena and subcooling. Traditional methods or in “house” methods can be used for evaluating thermal properties, while stability can be estimated over time by using optical techniques. By considering this double approach, in this work thermal and structural analyses of Glauber salt based composite PCMs are conducted by means of non-conventional equipment: T-history method (thermal analysis) and Turbiscan (stability analysis). Three samples with the same composition (Glauber salt with additives) were prepared by using different sonication times and their thermal performances were compared by testing both the thermal cycling and the thermal properties. The stability of the mixtures was verified by the identification of destabilization phenomena, the evaluation of the migration velocities of particles and the estimation of variation of particle size.
Keywords: Light--Scattering.